Land cover changes and their biogeophysical effects on climate. (21st June 2013) - Mahmood, Rezaul; Pielke, Roger A.; Hubbard, Kenneth G.; Niyogi, Dev; Dirmeyer, Paul A.; McAlpine, Clive; Carleton, Andrew M.; Hale, Robert; Gameda, Samuel; Beltrán‐Przekurat, Adriana; Baker, Bruce; McNider, Richard; et al.
ABSTRACT Land cover changes (LCCs) play an important role in the climate system. Research over recent decades highlights the impacts of these changes on atmospheric temperature, humidity, cloud cover, circulation, and precipitation. These impacts range from the local‐ and regional‐scale to sub‐continental and global‐scale. It has been found that the impacts of regional‐scale LCC in one area may also be manifested in other parts of the world as a climatic teleconnection. In light of these findings, this article provides an overview and synthesis of some of the most notable types of LCC and their impacts on climate. These LCC types include agriculture, deforestation and afforestation, desertification, and urbanization. In addition, this article provides a discussion on challenges to, and future research directions in, assessing the climatic impacts of LCC.